Systematic Literature Review : Gerakan Three Second Pause dalam Membangun Budaya Sopan Santun dan Tata Krama Peserta Didik di SMP Notre Dame Grand Wisata - Nordianus Wilfridus; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
The culture of politeness and etiquette are important aspects in the character education of students. This article discusses the implementation of the Three Second Pause movement at SMP Notre Dame Grand Wisata as an innovative method to build this culture. This movement encourages students to pause for three seconds before responding or acting, allowing them to think and act more mindfully. Through socialization, practical exercises, and feedback from teachers, this movement has proven to enhance positive interactions among students, reduce conflicts, and foster better character development. As a result, SMP Notre Dame Grand Wisata has successfully created a more polite and respectful learning environment. This article also provides recommendations for the sustainability of the program in building a culture of politeness in schools.